Water reuse for resilience: using scientific evidence for water reuse inclusive policy formulation in Lebanon - Al-Zu’bi, Maha; Tawfik, Mohamed; Brouziyne, Youssef; Moussallem, M. (International Water Management Institute, 2024)
Reusing treated wastewater for agricultural irrigation is a key strategy to build resilience in the Middle East and North Africa (MENA) region, particularly in Lebanon. As Lebanon faces a widening gap in water supply and demand, its agricultural sector is increasingly at risk. The country's 2024 National Water Sector Strategy identifies water reuse as one part of the solution to this crisis. However, despite years of investment in water and sanitation, Lebanon still lacks the necessary infrastructure, policies, regulatory frameworks, and institutional support. The International Water Management Institute (IWMI) plays a pivotal role in bridging science and policy, offering technical expertise to Lebanese counterparts through the CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA). IWMI’s efforts focus on developing Lebanon's first tailor-made water reuse standards for agriculture, which are crucial for addressing water scarcity and enhancing food security. While IWMI provides guidance, the responsibility for endorsing and adopting these standards lies with Lebanon’s national regulatory agencies and government authorities. Establishing these standards is critical for ensuring water security and sustainable agriculture, particularly given the region’s environmental challenges. This policy brief outlines key recommendations for integrating treated wastewater into Lebanon's Water-Energy-Food-Ecosystem (WEFE) Nexus: (1) safeguarding environmental and public health, (2) implementing robust monitoring and evaluation processes, (3) creating business incentives, (4) ensuring inclusive design and implementation, and (5) formulating science-based public policies.